Profitability, Share Return, Company Size, Industry Type and Corporate Social Responsibility Disclosure of Malaysian Public Listed Companies - Hafiz Bin Rosli, Mohamad; Farahwahida Binti Mohd, Dr. (International Journal of Engineering and Technology, 2018)
Over the years, the awareness of Corporate Social Responsibility (CSR) has been increasing and viewed as an integral part of the business to cater to the increasing expectations for a wide spectrum of stakeholders in pursuing their trade responsibly. The purpose of this article, first, is to determine the extend of Corporate Social Responsibility Disclosure (CSRD) among Malaysian Public Listed Companies (PLCs) and to examine whether profitability, share return, company size and industry type have any influence on the CSRD. Secondary data obtained from 100 public listed companies across industries were analysed and reported in this study. The constructed CSRD checklist was used to identify the focus level of CSRD, while multiple regression is employed to test the proposed hypotheses. The finding indicates that the highest and least disclosures were community and marketplace disclosure, respectively. It also remarks that, the profitability, share return and company size are found to have significanct relationships with the CSRD. It also noted that the industry type was not significantly linked to the CSRD. This finding could benefit the government and policy makers to consistently encourage corporates to practice CSR and to place appropriate emphasis awards for those who comply such as tax incentive, CSR awards; special rules exempted or granted government grants. Therefore, the corporations also need to move forward from just a voluntary disclosure to the betterment of nation sustainability.Â